2016
DOI: 10.1111/apt.13802
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of disease phase, treatment prescription and severe liver disease among 1598 patients with chronic hepatitis B in the Chronic Hepatitis Cohort Study, 2006–2013

Abstract: SUMMARY BackgroundLimited information exists regarding the distribution of disease phases, treatment prescription and severe liver disease among patients with chronic hepatitis B (CHB) in US general healthcare settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 29 publications
0
35
0
Order By: Relevance
“…The clinical stages of CHB are generally classified as the immune tolerant phase (IT), immune active phase (IA) and inactive CHB phase (IC) based on serum alanine aminotransferase (ALT), HBV DNA levels and HBeAg status [ 1 , 2 ]. Some patients cannot be classified into the above stages and fall into the grey zone (GZ) [ 3 ]. Current guidelines recommend the presence of an active liver inflammation using histology or elevated ALT serum levels greater than twofold the ULN plus elevated HBV DNA above 2000 IU/mL (HBeAg negative) or 20,000 IU/mL (HBeAg positive) as criteria for initiating antiviral therapy [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical stages of CHB are generally classified as the immune tolerant phase (IT), immune active phase (IA) and inactive CHB phase (IC) based on serum alanine aminotransferase (ALT), HBV DNA levels and HBeAg status [ 1 , 2 ]. Some patients cannot be classified into the above stages and fall into the grey zone (GZ) [ 3 ]. Current guidelines recommend the presence of an active liver inflammation using histology or elevated ALT serum levels greater than twofold the ULN plus elevated HBV DNA above 2000 IU/mL (HBeAg negative) or 20,000 IU/mL (HBeAg positive) as criteria for initiating antiviral therapy [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…12 Not surprisingly, patients with HBeAg-negative infection were older than those with HBeAg-positive infection, also similar to that reported from the USA. 13 In our study, the middle-aged group was the most predominant in both men and women. This is in line with the recent reports that the prevalence of HBsAg in childbearingaged men and women still being around 6% in rural and endemic areas in China.…”
Section: Discussionmentioning
confidence: 48%
“…Hadziyannis et al [15] [8]. In USA, Spradling et al reported 7% of inactive carriers and 0.6% of immunological tolerance in a study that included 1598 patients, where only 55% of whom were included [19]. In Cuba, Marlen et al found 7% of inactive carriers in a cohort study of 146 chronic HBV carriers [20].…”
Section: Discussionmentioning
confidence: 99%